2009
DOI: 10.1091/mbc.e09-01-0022
|View full text |Cite
|
Sign up to set email alerts
|

Divergent S Phase Checkpoint Activation Arising from Prereplicative Complex Deficiency Controls Cell Survival

Abstract: The DNA replication machinery plays additional roles in S phase checkpoint control, although the identities of the replication proteins involved in checkpoint activation remain elusive. Here, we report that depletion of the prereplicative complex (pre-RC) protein Cdc6 causes human nontransformed diploid cells to arrest nonlethally in G1-G1/S and S phase, whereas multiple cancer cell lines undergo G1-G1/S arrest and cell death. These divergent phenotypes are dependent on the activation, or lack thereof, of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Similar results were obtained by others in U2OS cells, where Chk1 activation and H2AX-p changes are not observed even though p53 is altered upon MCM loss and HU exposure (5). It has been shown that some cancer cells are apparently defective for fork stress/damage sensor mechanisms that involve ATR activation, resulting in sensitivity of such cancer cells to functional MCM loss in the absence of drug exposure (31). This suggests that tumor cells may differentially respond to MCM reduction and concurrent drug exposure dependent on the presence or absence of sensor pathways that ultimately produce changes in replication fork stress indicators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained by others in U2OS cells, where Chk1 activation and H2AX-p changes are not observed even though p53 is altered upon MCM loss and HU exposure (5). It has been shown that some cancer cells are apparently defective for fork stress/damage sensor mechanisms that involve ATR activation, resulting in sensitivity of such cancer cells to functional MCM loss in the absence of drug exposure (31). This suggests that tumor cells may differentially respond to MCM reduction and concurrent drug exposure dependent on the presence or absence of sensor pathways that ultimately produce changes in replication fork stress indicators.…”
Section: Resultsmentioning
confidence: 99%
“…Although the potential utility in suppressing MCM function is clear, an important problem must be considered in any clinical approach targeting MCM suppression over sustained time periods. Partial suppression of MCM function can result in reduced genomic stability and increased DNA damage (3, 5, 28, 31), and mice with sustained, partially defective MCM function display increased cancer risk (30). As such, extended MCM suppression during chemotherapy may be contraindicated for clinical management of cancer, with perhaps shorter durations of MCM co-suppression being more advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…64 The elevated in vivo association of pre-RC proteins with the 20mer1, 20mer2, and c-myc origins in the transformed cells may be the result of deregulation of the pre-RC checkpoint, causing certain origins to fire more than once per cell cycle, due to their improper licensing, leading to re-replication and thereby causing genetic instability and cancer. 65,66 In contrast, the equal in vivo association of pre-RC proteins with the lamin B2 origin in both transformed and normal cells indicates that this origin may remain unaffected by the aberrant deregulation of the pre-RC checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Cell Science 123 (2) contrast, it was reported that, when CDC6 is further depleted with more siRNAs (~100 nM), MCM loading is further reduced, leading to cell-cycle arrest around G1-S and/or cell death (Feng et al, 2003;Lau et al, 2009). Under such conditions, spontaneous Chk1 phosphorylation is observed.…”
Section: Cdc6 Depletion By Sirna Impairs Atr-dependent Replication-chmentioning
confidence: 99%